Development and Structure of Financial Sector in the Economy of the Islamic Republic of Iran - Seyed Hossein Mirjalili (Essays on Islamic Finance, 2008)
Financial Sector includes financial institutions, financial instruments, financial markets, regulations over the financial sector, and policy-making organizations in the financial sector. Financial institutions that collect deposits of the public are consist of governmental(governmental and developmental) and private banks, non-banking financial institutions, credit unions, and Gharz-ul-Hassanah Funds. Commercial insurance companies, social insurances, pension funds are contractual financial intermediaries within the Iranian economy. Investment companies that invest in securities act as investment financial institutions. In the money market, there exist banks, non-banking financial institutions, credit unions, and Gharz-ul-Hasanah Funds. The most important capital market institution in Iran is the Tehran Stock Exchange and there is no derivatives market. Financial instruments within the financial sector of the Iranian economy are stocks, Participation certificates of advantageous projects, and short term and long term deposits in banks. The major regulations over the financial sector in Iran are the law for interest-free banking operation, monetary and banking law, establishment law for securities exchange and the law for issuance methods of participation certificates, and the establishment law for central insurance of Iran and insurer. Some of the challenges within the financial sector of Iran are as follows: Bank-base-system of the financial sector, government's intervention in profit rate assignment and provision of compulsory facilities, lack of presence of private sector within the derivative market, taking effects of monetary policy from fiscal policies and the non-diversified securities within the capital market.
Keywords: 330; financial sector; Iran's economy; Islamic Banking; financial market; financial instrument; financial institution